Aerosol and Cloud Remote Sensing Observation in Limassol, Cyprus - Ene, Dragos; Poutli, Maria; Mettas, Christodoulos; Michaelides, Silas; Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Papoutsa, Christiana; Hadjimitsis, Diofantos G.; Buhl, Johannes; Seifert, Patric; Baars, Holger; Ansmann, Albert (My University, 2024)
In this paper, we present the new research infrastructure of the ERATOSTHENES CoE for aerosol and cloud remote sensing observations and its capabilities to participate in cal/val activities. The research facility is installed less than 2 km from the coastline of Limassol, Cyprus. The multiplatform for atmospheric research consists of a multiwavelength lidar, 35 GHz cloud radar, a microwave radiometer, and ancillary instruments to become a fully ACTRIS cloud and aerosol remote sensing station. Measurements performed at Limassol's station were already utilized for the validation of the aerosol products of Sentinel 5P and AEOLUS and will be used for the validation of the EarthCARE mission.
Keywords: EMMENA; atmosphere; cal/val; campaigns; spaceborne